Health-related quality of life measures used with Indigenous children/youth in the Pacific Rim: a scoping review - Sue Crengle; Trudy Sullivan; Emma H Wyeth; Sarah Derrett; Vicky Nelson; Georgia McCarty (BMJ Open)
Objective To identify and describe (1) which health-related quality of life (HRQoL) measures have been used with Indigenous children/youth (aged 8–17 years) within the Pacific Rim; and (2) studies that refer to Indigenous health concepts in the use of child/youth HRQoL measures.Design A scoping review.Data sources Ovid (Medline), PubMed, Scopus, Web of Science and CINAHL were searched up until 25 June 2020.Eligibility criteria Eligible papers were identified by two independent reviewers. Eligible papers were written in English, published between January 1990 and June 2020 and included an HRQoL measure used in research with Indigenous child/youth populations (aged between 8 and 17 years) in the Pacific Rim region.Data extraction and synthesis Data extracted included study characteristics (year, country, Indigenous population, Indigenous sample size, age group), HRQoL measure characteristics (generic or condition-specific measure, child or adult measure, who completed the measure(s), dimensions, items and response scale of measure) and consideration of Indigenous concepts (created for Indigenous population, modified for Indigenous population, validated for Indigenous population, reliability in Indigenous populations, Indigenous involvement, reference to Indigenous theories/models/frameworks).Results After removing duplicates, 1393 paper titles and abstracts were screened, and 543 had full-text review for eligibility. Of these, 40 full-text papers were eligible, reporting on 32 unique studies. Twenty-nine HRQoL measures were used across eight countries. Thirty-three papers did not acknowledge Indigenous concepts of health, and only two measures were specifically created for use with Indigenous populations.Conclusions There is a paucity of research investigating HRQoL measures used with Indigenous children/youth and a lack of involvement of Indigenous peoples in the development and use of HRQoL measures. We strongly recommend explicit consideration of Indigenous concepts when developing, validating, assessing and using HRQoL measures with Indigenous populations.